2020
DOI: 10.2967/jnumed.119.240598
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Response to Transarterial Chemoembolization in Hepatocellular Carcinoma Using 18F-Fluorothymidine PET

Abstract: Accurate disease monitoring is essential following transarterial chemoembolization (TACE) in hepatocellular carcinoma (HCC) due to potential for profound adverse event and large variation in survival outcome. Post-treatment changes on conventional imaging can confound determination of residual/recurrent disease, magnifying the clinical challenge. Based on increased expression of thymidylate synthase (TYMS), thymidine kinase-1 (TK-1) and SLC29A1 (Equilibrative nucleoside transporter 1, ENT1) in HCC compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…This was then followed by tracer injection (a maximum dose of 370MBq of [ 18 F]D4-FCH) and dynamic imaging (single-bed position over thorax and mediastinum) for 66 min followed by a half-body static (mid-thigh to vertex) attenuation CT and PET scan (3 min per bed position). Discrete venous bloods and plasma (at 5, 10, 15, 30, 60 min post injection) were obtained for radioactivity counting and metabolite analysis, as previously described 16 , 17 and applied in oncological studies 18 , 19 . The time course of metabolite and parent fraction measured directly by HPLC (experimental data) for D4 Choline are summarized in Figure S1 .…”
Section: Experimental Designmentioning
confidence: 99%
“…This was then followed by tracer injection (a maximum dose of 370MBq of [ 18 F]D4-FCH) and dynamic imaging (single-bed position over thorax and mediastinum) for 66 min followed by a half-body static (mid-thigh to vertex) attenuation CT and PET scan (3 min per bed position). Discrete venous bloods and plasma (at 5, 10, 15, 30, 60 min post injection) were obtained for radioactivity counting and metabolite analysis, as previously described 16 , 17 and applied in oncological studies 18 , 19 . The time course of metabolite and parent fraction measured directly by HPLC (experimental data) for D4 Choline are summarized in Figure S1 .…”
Section: Experimental Designmentioning
confidence: 99%
“…PET/CT imaging with 18 F-FLT, which reflects cell proliferation, is a non-invasive imaging method and has been used for the response evaluation ( 24 , 25 , 26 , 27 ). In addition to complex and competing factors in the FLT uptake mechanism, there are notable differences between patient preparation, imaging time after injection, protocol, amount of injected activity, reconstruction method, analysis techniques, timing before and after treatment, patient numbers, and disease groups in studies with F- 18 FLT PET/CT ( 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies investigating the role of FLT PET/CT in evaluating the liver-specific treatment response, considering high background liver uptake especially in HCC patients that hamper the detection of liver/lesions. Studies evaluated therapy of TACE-receiving HCC patients and systemic chemotherapy-receiving liver metastatic colorectal cancer patients ( 28 , 29 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this physiologic retention in the liver, Eckel et al [18] reported a median 20% higher focal uptake by malignant tumors than the surrounding liver, leading to a 69% sensitivity for the detection of HCC. To optimize the tumor-to-liver contrast, Sharma et al proposed in a pilot study to classified each voxel according to their time activity curve [42]. However, they showed that the high and variable SUV limited the improvement of tumor visualization.…”
Section: Discussionmentioning
confidence: 99%